ANALISIS PENGARUH IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP ECONOMIC VALUE ADDED (EVA) PERUSAHAAN DI INDONESIA - , Diana Vita Marina; , Dr. Hardo Basuki, M.Soc. Sc, Ak, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The concept of corporate social responsibility (CSR) has provided guidance that the company is no longer the only entities that separate from its environment, but also a business entity is obliged to adapt culturally to their social environment. The Government has issued UU PT No. 40 of 2007 that company must report the progress in relation to social responsibility and also on environmental issues. Economic Value Added (EVA) is the appropriate method to measure the value of the company. EVA able to reflect real business value the company because it involves counting the cost of capital which reflects the returns that are required to cover the risk faced by the company. The purpose of this research examines differences in the implementation of Corporate Social Responsibility (CSR) before and after UU PT No.40 of 2007, examine the differences Economic Value Added (EVA) before and after UU PT No.40 of 2007, and examines the effect of the implementation of Corporate Social Responsibility (CSR) to the Economic Value Added (EVA). The sample of this study using purposive sampling method from the companies listed in Indonesia Stock Exchange period 2005-2009. There are 180 companies during the period 2005-2009 that represent a sample of the research. The method of analysis in this research using descriptive and statistical analyzes. The results showed that there are differences in CSR & EVA corporation before UU PT No.40 of 2007 and after UU PT No.40 of 2007. No significant influence between CSR and corporate financial performance that measured with EVA.